Prevalence of type 2 diabetes mellitus (T2DM) in India: A systematic review (1994–2018). Issue 5 (September 2020) - Atre, Sachin; Deshmukh, Sona; Kulkarni, Manjusha
Abstract: Aim: To conduct a systematic and critical review of published studies on prevalence of Type 2 diabetes mellitus (T2DM) in urban and rural areas of India. Methods: We conducted a literature search in PubMed, EMBASE and Web of Science using the terms 'prevalence', 'Type 2 diabetes, 'India', 'urban' and 'rural' for English language articles published during January 1994–December 2018. We selected articles that reported the results of original studies that randomly sampled adults aged 15–80 years, and which reported T2DM prevalence based on the actual examination of blood samples. Results: Of 1751 articles screened by titles and abstracts, 37 fulfilled our inclusion criteria. Majority (28 of 37; 76%) of studies were from South India, especially from the states of Tamil Nadu, Andhra Pradesh, Kerala and Karnataka. The prevalence of T2DM showed a wide range from 1.9% to 25.2%. Only 11 studies covering 24 regions separately reported the data by urban or rural location. Albeit inconsistent, 17 studies reported prevalence of T2DM by age group. Conclusion: In this systematic review, we show that there remains an ambiguity about the actual prevalence of T2DM from India due to several factors. The findings underscore a strong need for having periodic regional surveillance involving appropriate epidemiological methods. Highlights: In this systematic review we show that due to differences in methods used for determining diabetes status, small sample sizes, inconsistency in determining the prevalence, there remains an ambiguity about the actual prevalence of type 2 diabetes mellitus (T2DM) from India. These findings underscore a strong need for having periodic nationwide and regional surveillance involving appropriate epidemiological methods for sampling and determining accurate prevalence of T2DM in India.